Effect of Eclipta alba and Ocimum sanctum on haloperidol induced parkinsonism - Chahal, Harmel Singh; Sharma, Shailendra (Journal of Drug Delivery and Therapeutics, 2018)
The aim of the study is protective effect of compound Eclipta alba and Ocimum sanctum on Parkinsonism induced mice by haloperidol injection. Parkinsonism is neurodegenerative disease due to the deficiency of dopamine in brain. The pathological hallmark of Parkinson’s disease in the cell loss within substantia nigra pars compacta (SNpc) region and the disease is charactrised by bradykinesia, rigidity, postural instability, orofacial dyskinesia, muscular stiffness and tremor1. Mice were injected 1mg/kg haloperidol and then treated with test and standard substance for 15 days. The impairment in catatonia in mice were tested using catatonic activity. Biochemical analysis of brain homogenate was performed so ass to assess brain Thiobarbituric acid reactive substance (TBARS) level and reduced glutathione (GSH) and TNF-α level were measured to assess total oxidative stress. EA 300mg/kg and OS 400mg/kg show slightly change in catatonic activity in mice while EA 600mg/kg and 800mg/kg significantly change in catatonic activity. Furthermore, Eclipta alba and Ocimum sanctum prevent the haloperidol induced changes in the level of brain TBARS, GSH and TNF-α. From the results we conclude that Eclipta alba and Ocimum sanctum has protective action against impairment in catatonic activity and pathological damage due to oxidative stress induced by intraperitoneally injection of haloperidol in mice.       Keywords: Eclipta alba, Ocimum Sanctum, Parkinsonism, Anti-oxidant.